Synthesis and Characterization of Empty Silicon Clathrates for Anode Applications in Li-ion Batteries. Issue 45 (9th June 2016) - Chan, Kwai S.; Miller, Michael A.; Ellis-Terrell, Carol; Chan, Candace K.
ABSTRACT: Several processing methods were developed and evaluated for synthesizing empty silicon clathrates. A solution synthesis method based on the Hofmann-elimination oxidation reaction was successfully utilized to produce 20 mg of empty Si46 . Half-cells using the Si46 electrodes were successfully cycled for 1000 cycles at rate of 5.3C. The capacity of the Si46 electrode in long-term tests was 675 mAh/g at the 4 th cycle, but increased to 809 mAh/g at 50 cycles. The corresponding Coulombic efficiency was better than 99%. The capacity dropped from 809 to 553 mAh/g after 1000 cycles while maintaining a 99% Coulombic efficiency. In comparison, a Ba8 Al8 Si38 electrode could be cycled for about 200 cycles with a lower capacity and Coulombic efficiency. Potential applications of empty silicon clathrates as anode materials in Li-ion batteries are discussed.